2021
DOI: 10.1002/jcla.23986
|View full text |Cite
|
Sign up to set email alerts
|

Combination of anlotinib and gemcitabine promotes the G0/G1 cell cycle arrest and apoptosis of intrahepatic cholangiocarcinoma in vitro

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 24 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Recent preclinical study has demonstrated synergistic cytotoxic effects of anlotinib in combination with the chemotherapeutic drug 5-FU against small cell lung cancer, both in vitro and in vivo(28). The combination of anlotinib and gemcitabine signi cantly inhibited the growth of ICC cells and induced cell apoptosis (29). In addition, anlotinib inhibited the proliferation, migration and invasion of BRCA cells and induce cell apoptosis by downregulating TFAP2C (30).…”
Section: Discussionmentioning
confidence: 98%
“…Recent preclinical study has demonstrated synergistic cytotoxic effects of anlotinib in combination with the chemotherapeutic drug 5-FU against small cell lung cancer, both in vitro and in vivo(28). The combination of anlotinib and gemcitabine signi cantly inhibited the growth of ICC cells and induced cell apoptosis (29). In addition, anlotinib inhibited the proliferation, migration and invasion of BRCA cells and induce cell apoptosis by downregulating TFAP2C (30).…”
Section: Discussionmentioning
confidence: 98%
“…To further investigate the efficacy of liensinine in treatment of ICC, we tried to combine liensinine with gemcitabine. Based on existing studies, 43–45 we set the concentration of gemcitabine on RBE and Hucc‐T1 to 10μM. Through colony formation test, wound healing assays, migration and invasion Transwell experiments, we found that, in RBE and Hucc‐T1 cells, liensinine combined with gemcitabine had certain curative effects on the proliferation, as well as on migration and invasion (Figures ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on existing studies, [43][44][45] tumor resistance to gemcitabine, [46][47][48][49] and therapy targeting on HIF-1a may improve the efficacy of gemcitabine. 50,51 Besides, available data does not rule out the possibility that gemcitabine directly or indirectly acts on HIF-1a.…”
Section: Liensinine Reversed the Emt Phenotype Of Icc Cells With High...mentioning
confidence: 99%
“…The G1-phase cell cycle arrest observed at 5 μΜ concentration suggests a cell-cycle specific nature observed in Gem treatments. The cell cycle arrest at G1-phase revealed in our study could account for an increase in number of cells at the G1-phase which prevented the progression of cells into the S-phase to undergone DNA synthesis [ 57 ]. Previously, we demonstrated 4NSG’s ability to induce early apoptosis in pancreatic cancer cell at higher treatment concentrations [ 58 ].…”
Section: Discussionmentioning
confidence: 99%